A review of species names combined with the genus name Coccus Linnaeus (Hemiptera: Sternorrhyncha: Coccoidea) - Williams, Douglas J.; Ben-Dov, Yair (Zootaxa, 2009)
Scale insect names combined with the genus name Coccus Linnaeus, number almost 550. These names are listed and annotated after searching the relevant taxonomic and economic literature published since 1758. Where possible, we give the current status for each name and discuss names of species that we regard as unrecognisable. We transfer Coccus stipulaeformis Haworth to the genus Ceroplastes as Ceroplastes stipulaeformis (Haworth) comb. n., and we also synonymise Coccus alchemillae Walker with Porphyrophora polonica (Linnaeus) syn. n., Coccus conchiformis Gmelin with Coccus conchiformis Goeze syn. n., Coccus clematitis Goeze with Parthenolecanium persicae persicae (Fabricius) syn. n., Coccus mespili Goeze with Pulvinaria vitis (Linnaeus) syn. n., Coccus arbuti Turton with Eriococcus uvaeursi (Linnaeus) syn. n., and Coccus cacti v. silvestris Meunier with Dactylopius tomentosus (Lamarck) syn. n..